Pemanfaatan Sumber Belajar Lingkungan Sekitar sebagai Media dalam Pembelajaran IPS di Sekolah Dasar - Hana Heasdiana; Ruby Tri Maharani; Syifa Ifadilah; Oman Fahrurohman (Mathematics Education Study Program, 2025)
This study aims to investigate the use of the surrounding environment as a learning resource in Social Studies School. The research employs a qualitative approach with a phenomenological type. To achieve this goal, interviews were conducted with teachers and students, and supporting documents were also analyzed. The research findings reveal that the surrounding environment, such as the school garden and community social activities, can serve as a relevant and significant learning resource. Environment-based learning is considered more engaging and easier to understand, resulting in positive responses from students. Nonetheless, there are several challenges encountered. These challenges include limited time, unstable weather conditions, lack of coordination among students, and inadequate facilities. Teachers need to plan well, use alternative learning media, and establish clear roles.In group activities, and by making the best use of school facilities. This study shows that environment-based social studies learning can create a dynamic learning atmosphere, relevant to students' daily lives, and has the potential to enhance their conceptual understanding and social skills.